Strasbourg's inclusive policies for migrants and the IBA urban developmental paradigm. - Siebert, Tristan (My University, 2020)
The city centre of Strasbourg is crossed by a major motorway, which is constantly congested and polluted. The public authorities wish to transform the route into a boulevard as well as to develop surrounding areas. Currently, the numerous vacant spaces around the transport infrastructure are used by various associations, whose right of residency is relatively unsettled. An increasing number of small illegal settlements can also be found here as well as in adjacent neighbourhoods. While the city council is implementing inclusive policies towards migrants, how can these issues be translated locally into urban planning tools? Strasbourg is an important transit point for migrants between France and Germany. Further, due to its border location, the city has always been an important hub for the exchange of ideas; in particular, new concepts of urban planning find fertile ground here. In order to transform the motorway, the public authorities intend to implement the German urban development tool known as the International Building Exhibition (German: Internationale Bauausstellung or IBA).

Die Arbeit untersucht die IBAs von Hamburg und Berlin vor dem Hintergrund der Frage, ob sich das Konzept IBA auf die Stadtplanung Straßburgs übertragen lässt.
Keywords: Stadtentwicklungsplanung; Stadterneuerung; Stadtentwicklungskonzept; Inklusion; Internationale Bauausstellung